Investigating the Correlation of the U.S. Air Force Physical Fitness Test to Combat-Based Fitness: A Women-Only Study. Issue 6 (1st June 2014) - Mitchell, Tarah; White, Edward D.; Ritschel, Daniel
ABSTRACT: The primary objective in this research involves determining the Air Force Physical Fitness Test's (AFPFT) predictability of combat fitness and whether measures within the AFPFT require modification to increase this predictability further. We recruited 60 female volunteers and compared their performance on the AFPFT to the Marine Combat Fitness Test, the proxy for combat fitness. We discovered little association between the two ( R 2 of 0.35), however, this association significantly increased (adjusted R 2 of 0.56) when utilizing the raw scores of the AFPFT instead of using the gender/age scoring tables. Improving on these associations, we develop and propose a simple ordinary least squares regression model that minimally impacts the AFPFT testing routine. This two-event model for predicting combat fitness incorporates the 1.5-mile run along with the number of repetitions of a 30-lb dumbbell from chest height to overhead with arms extended during a 2-minute time span. These two events predicted combat fitness as assessed by the Marine Combat Fitness Test with an adjusted R 2 of 0.82. By adopting this model, we greatly improve the Air Force's ability to assess combat fitness for women.